Localization using LEO satellites - Xia, Yingyu (2014)
Localization have been commonly performed utilizing signals from navigational satellites such as the Global Positioning System (GPS). However, in an urban environment this proves to be a challenge where GPS signals were known to deteriorate significantly [1] [2]. In an attempt to improve the localization reliability, this project explores the feasibility of using Low Earth Orbit (LEO) satellites for positioning services.